Introduksi Peralatan Pencetak Pada Industri Patilo - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT One of the major restrictions to increase patilo production is the low capacity in patilo forming process, because this process is still carried out manually. The following research was intended to introduce mechanical patilo forming equipment in order to increase forming process capacity as one of the method to improve production capacity in patilo industry. The result from the following research is mechanical forming equipment which can be used in the forming process in patilo industry. Basically this equipment works by turning and pressing patilo dough in the cylindrical container above a perforated plate. The result of the operating equipment showed that it could satisfy the requirements, which were low operational cost, did not cause pollution and danger, patilo product was clean, hygienic, and equal. Based on the observation result on one cycle forming process, the equipment could increase the capacity of patilo forming process about five times composed to the manual process. Keywords: patilo, forming, mechanical, capacity, production